ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s, 1985)
News; Desmond Tutu, Nobel Prize and institutional racism; Preparatory course for German teachers going to Zimbabwe; and African music.
Keywords: Political News; Entertainment